Therapeutic Strategies for Sleep Apnea in Hypertension and Heart Failure - Akiko Noda; Seiko Miyata; Yoshinari Yasuda (Pulmonary Medicine)
Sleep-disordered breathing (SDB) causes hypoxemia, negative intrathoracic pressure, and frequent arousal, contributing to increased cardiovascular disease mortality and morbidity. Obstructive sleep apnea syndrome (OSAS) is linked to hypertension, ischemic heart disease, and cardiac arrhythmias. Successful continuous positive airway pressure (CPAP) treatment has a beneficial effect on hypertension and improves the survival rate of patients with cardiovascular disease. Thus, long-term compliance with CPAP treatment may result in substantial blood pressure reduction in patients with resistant hypertension suffering from OSAS. Central sleep apnea and Cheyne-Stokes respiration occur in 30–50% of patients with heart failure (HF). Intermittent hypoxemia, nocturnal surges in sympathetic activity, and increased left ventricular preload and afterload due to negative intrathoracic pressure all lead to impaired cardiac function and poor life prognosis. SDB-related HF has been considered the potential therapeutic target. CPAP, nocturnal O2 therapy, and adaptive servoventilation minimize the effects of sleep apnea, thereby improving cardiac function, prognosis, and quality of life. Early diagnosis and treatment of SDB will yield better therapeutic outcomes for hypertension and HF.